The Influence of Profitability and Company Size on Capital Structure in Infrastructure Sector BUMN Companies Listed on the IDX 2017-2022 - Ilyas Alfian Suhadi (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to determine the effect of profitability and company size on capital structure. This type of research is quantitative and uses secondary data. Then the data analysis technique in this research uses descriptive statistics, classical assumption testing, and hypothesis testing. The sample in this research is state-owned companies listed on the IDX, especially in the infrastructure sector in the 2017–2022 period. The number of samples used in the research was 42. The research results show that profitability has a significant positive effect on capital structure, and company size has a significant positive effect on capital structure.